Communication and Conflict of North Coast Resources Utilization in Serang Regency - Muldi, Ail; Sumardjo, Sumardjo; Kinseng, Rilus A; Sugihen, Basita Ginting (Universitas Negeri Semarang, 2019)
The gap in the coastal resources utilization on the North Coast in Serang Regency has the potential to cause conflict between coastal communities dealing with local governments and sea sand mining companies. This research focuses on how the communication practices of the conflicting parties and the typology of conflict, communication interactions in conflict relations and communication strategies in conflict solutions. The research used qualitative approach which was conducted through in-depth interview with informants purposively. The results of the research showed that the dominance of natural resources was the trigger for conflict in the utilization of coastal resources on the North Coast in Serang Regency. The ineffectiveness of government and company communication in managing conflict potentials made coastal communities perceived the sea sand mining activities negatively. Coastal communities fought for their interests in various forms namely demonstrations, anarchism, social conflict between layers and human rights violations. The most active community groups were fishermen because sea sand mining had caused technical problems with fishing and decrease in income. The conflicting parties communicated with each other openly, defensively and in confrontational way. The practice of communication in resolving conflicts ran less effectively because the government and the company did not involve conflicting parties through communication to resolve the conflict. The research findings are the basis of understanding to manage potential conflicts and its escalations through appropriate communication to reach consensus to realize convergence of interests.